2014
DOI: 10.1371/journal.pone.0092395
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Risk Module Identification and Module-Based Disease Risk Evaluation: A Case Study on Lung Cancer

Abstract: Gene expression profiles have drawn broad attention in deciphering the pathogenesis of human cancers. Cancer-related gene modules could be identified in co-expression networks and be applied to facilitate cancer research and clinical diagnosis. In this paper, a new method was proposed to identify lung cancer-risk modules and evaluate the module-based disease risks of samples. The results showed that thirty one cancer-risk modules were closely related to the lung cancer genes at the functional level and interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…For example, the gene H19 (cg21926276 locate) is related with both lung cancer and tumor growth, methylation of which has been thought as a sensitive marker of tobacco history [40,41]. The gene CDCA3 (cg27042065 located) is also associated with lung cancer and survival of cancer patients [42][43][44], and Song and Yang (2018) have reported that gene LOC338797 (cg26387355 located) is related with progression of tumor in lung cancer patients [45]. Besides confirming the previously reported genes, the three CpGs (cg21926276, cg27042065 and cg26387355) are also identified as novel markers for the survival of lung cancer patients.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…For example, the gene H19 (cg21926276 locate) is related with both lung cancer and tumor growth, methylation of which has been thought as a sensitive marker of tobacco history [40,41]. The gene CDCA3 (cg27042065 located) is also associated with lung cancer and survival of cancer patients [42][43][44], and Song and Yang (2018) have reported that gene LOC338797 (cg26387355 located) is related with progression of tumor in lung cancer patients [45]. Besides confirming the previously reported genes, the three CpGs (cg21926276, cg27042065 and cg26387355) are also identified as novel markers for the survival of lung cancer patients.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…A new method was also designed by Jia et al to identify cancer risk modules and assess disease risks based on the modules in the samples [77]. A co-expression network was first constructed followed by the identification of candidate modules and their associated cancer risk.…”
Section: Lung Cancer (Lc)mentioning
confidence: 99%
“…Gene co-expression network analysis is a popular technique, widely used in several articles to model dependency structure among gene expression, such as: used to investigate the changes of expression patterns across the disease progression stages [5], [6], [7], [8], [9], [10], [11], used to identify hub genes and relevant pathways [12], [13], used to distinguish cancer risk modules [14] and utilized for biomarker selection in cancer prognosis [15]. Gene co-expression analysis in different stages of HIV progression is noticed to be carried out in literatures [5], [7], [16].…”
Section: Introductionmentioning
confidence: 99%